SAT0099 Sarcopenia is associated with joint damage in rheumatoid arthritis: a cross-sectional study. (12th June 2018) - Lin, J.-Z.; Wang, Y.-Y.; Liu, P.-J.; Mo, Y.-Q.; Li, Q.-H.; Cheng, W.-M.; He, X.-L.; Dai, L.
Abstract : Background: The association of metabolic status with disease characteristics of rheumatoid arthritis (RA) remain controversial. Body composition (BC) instead of body mass index (BMI) has been more and more recommended to assess metabolic status. Objectives: To investigate the characteristics of BC in RA patients and their association with RA disease characteristics. Methods: BC was assessed in RA patients and control subjects by bioelectric impedance analysis. Overfat was defined by body fat percentage (BF%) as ≥25% for men and ≥35% for women. Sarcopenia was defined by skeletal muscle mass index (SMMI)≤8.87 kg/m 2 in men and ≤6.42 kg/m 2 in women. Clinical data including disease activity, function and radiographic assessment were collected. Results: There were 457 RA patients and 1, 860 control subjects recruited. In RA patients, there were 17.7%, 58.0%, 20.1% and 4.2% with underweight, normal weight, overweight, or obesity respectively, and 32.4% were overfat, 11.4% with sarcopenia. Comparisons to control subjects in age and gender stratification showed that male RA patients had significantly lower BMI and SMMI with higher percentage of underweight and sarcopenia in almost all age subgroups; female patients had lower SMMI in all age subgroups and lower BMI with higher prevalence of sarcopenia but higher BF% at age ≤30 and 51–60 years (all P<0.05, figure 1). RA patients with sarcopenia had higher rate of functional limitation, higher disease activity indicators and radiographic scores (all P<0.05, table 1). Multivariate logistic regression analyses showed SMMI ( OR =0.633, 95% CI : 0.507 0.790, P <0.001) and sarcopenia ( OR =2.154, 95% CI : 1.032 4.497, P =0.041) were associated with radiographic joint damage. Conclusions: This study showed lower SMMI and higher prevalence of sarcopenia in RA patients which were positively associated with joint damage. Disclosure of Interest: None declared